Jordan Economic Monitor, Spring 2015 : Persisting Forward Despite Challenges - World Bank (Washington, DC, 2015)
Jordans economy continues to slowly but steadily recover from the Arab Spring spillovers. These spillovers include Egypts gas disruptions, the neighboring Syrian and Iraqi conflicts and associated security incidents. Notwithstanding these shocks, real GDP growth rate is estimated to have reached 3.1 percent in 2014, up 30 basis points over 2013. From the supply side, growth was led by construction, wholesale and retail trade, and finance and insurance, with a pick-up in the mining and quarrying sector. On the demand side, growth was predominantly fueled by higher public investments, mostly due to earmarked GCC grants, and a narrower trade deficit. The steady economic recovery has improved unemployment rates although this masks underlying structural weaknesses. While unemployment dropped from 12.6 to 11.9 percent from 2013 to 2014, this was not driven by increased employment but by an equivalent and concerning drop in the labor force participation rate. This was possibly driven by discouraged workers given perceived competition from refugees and limited hiring prospects in the public sector given ongoing consolidation efforts.